Effect of LI4 Acupressure on Labor Pain in the First Stage of Labor in Nuliparous Women - M Kordi; M Firoozi; H Esmaili (Tehran University of Medical Sciences, 2011)
Background & Objective: Labor pain management is one of the most important procedures of midwifery cares. Acupressure, a non-pharmacological method of labor pain relief, is an available, easy to use, inexpensive, and without side effect method of pain relief. The purpose of this study was to compare the effects of LI-4 acupressure on labor pain in women during first stage of labor. Methods & Materials: A single blind randomized clinical trial study was carried out on 83 primipara women. The inclusion criteria were singleton pregnancy in 38-42 weeks of gestation, cephalic presentation, and spontaneous uterine contractions. Participants were divided into three groups including acupressure group, touch group, and the usual care (control group). The intensity of labor pain was measured using visual analog scale with the rating from 0-100 mm immediately, 30 minutes, and one hour after the intervention during the first stage of labor. Data were analyzed using statistical tests of ANOVA, Chi-square, and Exact chi-square. Results: Findings indicated that acupressure group had lower labor pain in the active phase of the first stage of labor immediately after intervention than the other groups (P=0.026). Conclusion: The results of this study suggested that LI4 acupressure reduced the intensity of labor pain in the first stage of labor without any side effects to mother and infant. This procedure can be used as a simple, safe and inexpensive method to relief labor pain.